Evaluasi kebijakan pendidikan dan peran dalam meningkatkan kualitas pendidikan - azmi, arida ulul (Maliki Interdisciplinary Journal, 2025)
Education policy in Indonesia underwent significant transformation with the shift from Law No. 2 of 1989 to Law No. 20 of 2003. This transition was driven by the need to address challenges such as religion-based education, equitable access, quality improvement, and management efficiency (Anjelina et al., 2021). During the reform era, education policies embraced democratization through initiatives like School-Based Management (SBM) and community participation, aiming to decentralize decision-making and empower schools and local communities (Rozak, 2021). Other policy changes included the replacement of the National Final Exam (EBTA) with School Final Exams (UAS) and National Exams (UN) to enhance quality, alongside a shift from quantity-focused to quality-oriented education (Rozak, 2021). This study highlights the dynamics of education policy evolution and its implications for the national education system.